What if negative emission technologies fail at scale? Implications of the Paris Agreement for big emitting nations. (3rd July 2018) - Larkin, Alice; Kuriakose, Jaise; Sharmina, Maria; Anderson, Kevin
ABSTRACT: A cumulative emissions approach is increasingly used to inform mitigation policy. However, there are different interpretations of what '2°C' implies. Here it is argued that cost-optimization models, commonly used to inform policy, typically underplay the urgency of 2°C mitigation. The alignment within many scenarios of optimistic assumptions on negative emissions technologies (NETs), with implausibly early peak emission dates and incremental short-term mitigation, delivers outcomes commensurate with 2°C commitments. In contrast, considering equity and socio-technical barriers to change, suggests a more challenging short-term agenda. To understand these different interpretations, short-term CO2 trends of the largest CO2 emitters, are assessed in relation to a constrained CO2 budget, coupled with a 'what if' assumption that negative emissions technologies fail at scale. The outcomes raise profound questions around high-level framings of mitigation policy. The article concludes that applying even weak equity criteria, challenges the feasibility of maintaining a 50% chance of avoiding 2°C without urgent mitigation efforts in the short-term. This highlights a need for greater engagement with: (1) the equity dimension of the Paris Agreement, (2) the sensitivity of constrained carbon budgets to short-term trends and (3) the climate risks for society posed by an almost ubiquitous inclusion of NETs within 2°C scenarios. POLICY RELEVANCE Since the Paris meeting, there is increased awareness that most policy 'solutions' commensurate with 2°C include widespread deployment of negative emissions technologies (NETs). Yet much less is understood about that option's feasibility, compared with near-term efforts to curb energy demand. Moreover, the many different ways in which key information is synthesized for policy makers, clouds the ability of policy makers to make informed decisions. This article presents an alternative approach to consider what the Paris Agreement implies, if NETs are unable to deliver more carbon sinks than sources. It illustrates the scale of the climate challenge for policy makers, particularly if the Agreement's aim to address 'equity' is accounted for. Here it is argued that much more attention needs to be paid to what CO2 reductions can be achieved in the short-term, rather than taking a risk that could render the Paris Agreement's policy goals unachievable.